Expanding Valve Repair in Rheumatic Heart Disease - Afifi, Ahmed; Shehata, Nairouz; Nagi, Mohamed; Sultan, Abdel Rahman; Yacoub, Magdi (Frontiers in Cardiovascular Medicine, 2022)
Rheumatic heart disease is a serious ailment with significant morbidity and mortality in endemic areas yet, there is no agreement on the indication, timing, and surgical modality for treating rheumatic valve affection. There is mounting evidence that rheumatic mitral valve repair is possible with good long-term results, less is the case with rheumatic aortic valve disease. We discuss the surgical approach to both valves emphasizing the role of multimodality imaging.